2014
DOI: 10.1128/aac.02552-13
|View full text |Cite
|
Sign up to set email alerts
|

Selective Target Inactivation Rather than Global Metabolic Dormancy Causes Antibiotic Tolerance in Uropathogens

Abstract: Persister cells represent a multidrug-tolerant (MDT), physiologically distinct subpopulation of bacteria. The ability of these organisms to survive lethal antibiotic doses raises concern over their potential role in chronic disease, such as recurrent urinary tract infection (RUTI). Persistence is believed to be conveyed through global metabolic dormancy, which yields organisms unresponsive to external stimuli. However, recent studies have contested this stance. Here, various antibiotics that target different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 45 publications
(50 reference statements)
5
64
2
4
Order By: Relevance
“…The dramatic difference in ampicillin and norfloxacin killing results (compare Fig. 5 and 6) supports the assertion that elevated levels of (p)ppGpp induce antibiotic tolerance via antibiotic-specific pathways rather than protection from antibiotics in general (57, 7780). Although the role of (p)ppGpp in ampicillin tolerance is well established, (p)ppGpp's role in protection from gyrase inhibitors such as norfloxacin is controversial: although some studies, similar to our own results, report an absence of specific protection (81), other studies observed prominent effects (4, 82).…”
Section: Discussionsupporting
confidence: 65%
“…The dramatic difference in ampicillin and norfloxacin killing results (compare Fig. 5 and 6) supports the assertion that elevated levels of (p)ppGpp induce antibiotic tolerance via antibiotic-specific pathways rather than protection from antibiotics in general (57, 7780). Although the role of (p)ppGpp in ampicillin tolerance is well established, (p)ppGpp's role in protection from gyrase inhibitors such as norfloxacin is controversial: although some studies, similar to our own results, report an absence of specific protection (81), other studies observed prominent effects (4, 82).…”
Section: Discussionsupporting
confidence: 65%
“…Studies of longitudinal isolates from long-term chronic infections have also delivered indirect evidence that the evolution of persistence occurs in vivo. In long-term P. aeruginosa lung infections, selection for increased persister levels without an increase in resistance was reported (15), and similar observations were made in uropathogenic E. coli (52) and the fungal pathogen Candida albicans (53). However, no selection for increased persistence in Burkholderia species was seen during prolonged treatment of infected lungs (54).…”
Section: Figmentioning
confidence: 77%
“…Since most antibiotics target processes required for growth and division and consequently cells that are actively growing and dividing, persisters were suggested to be in a dormant or slow‐growing state . While this correlation between growth rate and persistence has been confirmed in several recent studies , it is also becoming evident that just being in a non‐growing state does not impart antibiotic tolerance . Also several studies, mostly using E. coli , have started identifying the key players involved in persistence and have started uncovering the mechanistic details of this process .…”
Section: Introductionmentioning
confidence: 99%